Components of Patient Satisfaction After Orthognathic Surgery. Issue 1 (January 2016) - Kufta, Kenneth; Peacock, Zachary S.; Chuang, Sung-Kiang; Inverso, Gino; Levin, Lawrence M.
Abstract : Abstract: The purpose of this study was to compare overall patient satisfaction after orthognathic surgery with the following specific categories: appearance, functional ability, general health, sociability, and patient–clinician communication. A 16-question survey was developed and administered to include patients at either 6 or 12 months after orthognathic surgery between June 2013 and June 2014 at the University of Pennsylvania and Massachusetts General Hospital. The predictor variables included age, sex, type of procedure, medical comorbidities, intra- or postoperative complications, and presence of paresthesia. The outcome variable was patient satisfaction overall and in each category based on a Likert scale (0: not satisfied at all to 5: very satisfied). A total of 37 patients completed the survey and had a high overall rate of satisfaction (100% of responses were 4 or 5 on Likert scale). Overall satisfaction had the highest correlation with appearance (ρ = 0.52, P  = 0.0009) followed by sociability (ρ = 0.47, P  = 0.004), patient–clinician communication (ρ = 0.38, P  = 0.02) functionality (ρ = 0.19, P  = 0.26), and general health (ρ = −0.11, P  = 0.51). Patients had high satisfaction scores for orthognathic surgery. Satisfaction with postoperative appearance had the strongest correlation with overall satisfaction.